Research on the applicability of an exercise rehabilitation app aiming to improve the mental and physical health of breast cancer patients in the post-operative period - Zhu, Jiaxin; Niu, Hu; Lu, Dianjie; Li, Yuqi; Ding, Meng (Frontiers in Psychology, 2023)
Purpose Breast cancer is one of the most common malignant cancers in women, seriously endangering the physical and mental health of patients. In this study, we developed an app for breast cancer patients undergoing radiotherapy or chemotherapy with a focus on exercise interventions, supplemented by nutritional and psychological interventions, to verify the applicability of the app for these patients and its impact on their quality of life, sleep, and psychological state. We also investigated the patients’ experience and perceptions of the app. Methods A total of 17 participants, aged 42–58 years, were recruited for this study using a mixed-methods design, including quantitative group pre-and post-test scores and qualitative interview results. The participants used the app for 8–18 weeks depending on their radiotherapy or chemotherapy cycle. During the radiotherapy or chemotherapy period, the participants used the “Yun Dong Ru Kang” exercise rehabilitation app to perform aerobic exercises twice a week, as well as rehabilitation exercises appropriate to their radiotherapy or chemotherapy stage, and used the app on their own the rest of the time. The primary results included their scores on the PSSUQ overall assessment usability questionnaire, the users’ use of the app, and the results of the interviews; the secondary indicators were quality of life, sleep status, and anxiety and depression status. Results An overall score of 6.2 (out of 7 points) on the PSSUQ questionnaire indicates the high usability; the average use time per subject per week was 97.69 ± 11.82 min, which exceeds the minimum use time, but the average use time tended to decrease as the use time was postponed. Promoted articles on nutritional diets received the most hits. The results of the interviews were consistent with the questionnaire scores, with the majority of participants believing that the means of exercise should be enriched and the interface optimized, while the reduction in the length of use was related to the participants’ own state of learning about calisthenics. In the results of the Breast Cancer-Specific Scale FACT-B, there was a significant increase (p < 0.05) in the Emotional Status dimension score and a significant decrease (p < 0.05) on the Additional Concerns dimension score. In the results of the Pittsburgh Sleep Quality Inventory PSQI, there was a non-significant improvement in all items except for a significant increase (p < 0.05) for the Hypnotic Medication item. In the Hospital Anxiety and Depression Scale (HADS), there was no significant improvement in any of the anxiety and depression factors. Conclusions The “Yun Dong Ru Kang “app has certain applicability, and the use of the exercise rehabilitation app may effectively reduce the negative impact of chemotherapy side effects on the quality of life, sleep and depression of breast cancer patients in the chemotherapy or radiotherapy phase. Before it is put into use in the future, the app should be enriched with exercise tools, the interface should be optimized, and articles on nutrition and diet should be promoted.